Upper secondary certificate, and then what? : Factors which induce upper secondary school leavers to enter vocational education and training - Schnitzler, Annalisa [Verfasser] (My University, 2019)
"In light of the rising numbers of students, this article investigates the question of which pupils are planning to commence a programme of VET despite being in possession of a higher education entrance qualification. Data from the German National Educational Panel Study (NEPS) is used to identify factors which encourage pupils in their twelfth school year to adopt such a plan. The findings show that influences from within the social environment, the vocational orientation process and evaluations of costs, benefits and opportunities undertaken by the young people are all of relevance. These results finally serve as a basis for the derivation of proposals for vocational orientation." (author's abstract; BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; S 1.3 Berufliche Erstausbildung; P 2.1.5 Fachhochschul- und Hochschulreife; Berufsorientierung; Berufsentscheidung; Berufsausbildung; Gymnasiast; Studienberechtigung; Nationales Bildungspanel